The Impact of Flexible Work Arrangements and Perceived Supervisor Support on Employee Performance: The Mediating Role of Work Engagement - Darmawan, Surya; Alawiyah, Lulu Mazdah (Faculty of Economics and Business, Universitas Klabat, 2024)
This study aims to explore the impact of Flexible Working Arrangements (FWA) and Perceived Supervisor Support (PSS) on Work Engagement (WE) and employee performance at Perfetti Van Melle Bogor. Additionally, the research evaluates the mediating role of WE in the relationship between FWA and PSS with employee performance. A quantitative method was employed, with the population consisting of all 200 employees at Perfetti Van Melle Indonesia. Data were collected through a questionnaire and analyzed using SEM-PLS. The results indicate that FWA and PSS have a significant positive effect on WE, with t-values of 3.814 and 3.499 and p-values of 0.000 and 0.001, supporting hypotheses H1 and H2. WE also significantly positively affect employee performance, with a t-value of 15.804 and a p-value of 0.000, supporting hypothesis H3. Moreover, FWA and PSS improve employee performance through WE as a mediator, with t-values of 3.425 and 3.404 and p-values of 0.001, supporting hypotheses H4 and H5. In conclusion, flexible work arrangements and supervisor support significantly influence work engagement, which in turn enhances employee performance. Work engagement serves as a mediator that strengthens the effect of these two factors on performance, highlighting the importance of FWA and supervisor support in boosting productivity.